Impact of intra-operative cell salvage on blood coagulation in high-bleeding-risk patients undergoing cardiac surgery with cardiopulmonary bypass: a prospective randomized and controlled trial. Issue 1 (December 2016) - Shen, Sheliang; Zhang, Jun; Wang, Wenyuan; Zheng, Jiayin; Xie, Yihong
Abstract Background Intra-operative cell salvage (CS) was reported to have no impairment on blood coagulation in low-bleeding-risk cardiac surgery with cardiopulmonary bypass (CPB), but studies in high-bleeding-risk cardiac surgery are limited. The objective of this study is to evaluate the impact of CS on blood coagulation in high-bleeding-risk cardiac surgery with CPB. Methods One hundred and ten patients were randomly assigned to either with intra-operative CS group (Group CS) or without intra-operative CS group (Group C). Study endpoints included the incidence of impairment of blood coagulation during perioperative period (peri-op) and the incidence of adverse events during postoperative period (post-op). Peri-op was defined as the period from beginning of anesthesia (anesthesia induction) to 24 h after end of surgery. Post-op was defined as the period from the end of surgery to 24 h after end of surgery. The types of impairment of blood coagulation included heparin residual, coagulopathy due to low PLT, coagulopathy due to low FIB, coagulopathy due to low coagulation factors, hyperfibrinolytic. The sum of above five types was total impairment of blood coagulation. Adverse events included excessive bleeding, resternotomy, etc. Results The incidence of heparin residual measured both at the end of surgery and during post-op were significantly higher in Group CS than in Group C (15.09 vs 4.00, 13.21 vs 2.00 %;p  = 0.024, 0.010, respectively). Similarly, the incidence of total impairment of blood coagulation at the end of surgery and during post-op were significantly higher in Group CS than in Group C (32.08 vs 18.00, 26.42 vs 12.00 %;p  = 0.043, 0.040, respectively). The incidence of excessive bleeding during post-op was 32.08 % in Group CS compared with 16.00 % in Group C (p  = 0.038). Intriguingly, CS was associated with a significantly increase in the relative risk ratios for heparin residual and excessive bleeding (p  = 0.034, 0.049, respectively). Conclusions Intra-operative CS could impair blood coagulation in the scenario of high-risk-bleeding cardiac surgery with CPB.